Radiocarbon Dates of Peats from North Pacific North America - Heusser, Calvin J. (Radiocarbon, 1959)
Ages are presented for 17 late-Pleistocene peat samples from sections that range from Karluk on Kodiak Island, Alaska to Port Orford, Oregon. Pollen and peat stratigraphy of the sections is used to interpret the environments prevailing at and since the time of sample deposition. The late-glacial at more southerly Pacific coastal Alaskan sites is dated at ca. 10,800 b.p. and the postglacial at ca. 10,000 b.p. At northerly coastal sites these intervals begin somewhat later. Regression rates for sealevel are given for a number of sites along this coast. Sample ages from two Oregon lakes suggest eustatic transgression ca. 5000 b.p. during the Hypsithermal interval.